Central Gulf of Aden conjugate margins (Yemen-Somalia): Tectono-sedimentary and magmatism evolution in hybrid-type margins. (July 2019) - Nonn, Chloé; Leroy, Sylvie; Lescanne, Marc; Castilla, Raymi
Abstract: Magma-rich and magma-poor passive margins are generally studied separately. Yet, the spatial evolution from one type to another is not well understood. Central Gulf of Aden margins are at the transition between these two types of margins. Based on new seismic data, published wells and gravity data, we determine seismic stratigraphy and structural patterns. We map the distinct crustal domains (continental, Ocean-Continent Transition (OCT), oceanic domains) and propose a tectonic evolution of the Yemeni and Somalian conjugate margins in an oblique rifting context. The most striking results are the significant segmentation, narrowness and asymmetry of conjugate margins, as well as the gradual eastward decrease in the intensity of magmatic activity of these hybrid-type margins. West of Bosaso-Hami Fracture Zone (BHFZ), the Hami-Ahl Medo segment presents magmatic-type margin features in the distal Yemeni margin related to the strong influence from the Afar plume: Seaward dipping reflectors develop since the late syn-rift stage (∼21-18 Ma) near the Xiis-Al Mukalla Fracture Zone. Conversely, east of BHFZ, the Bosaso-Sayhut margins segment is characterized by magma-poor margins for which the exhumation stage is characterized by the unroofing of mantle along multiple detachment faults in the OCT and shortly followed by diachronous volcanism (∼18 Ma). The central Gulf of Aden is affected by a major uplift during the final syn-rift stage and up to OCT formation. This event is associated with the formation of erosional surfaces in the east and with gravitational deformation taking place on decoupling surfaces at the base of the syn-rift sequence (lower Ghaydah Fm) that lead to the sliding of syn-rift units on top of the exhumed mantle rocks in the OCT.